Splintering South: Ecologically Unequal Exchange Theory in a Fragmented Global Climate - David Ciplet; J. Timmons Roberts (Journal of World-Systems Research, 2017)
The article examines the changing nature of politics in the United Nations climate negotiations through the lens of ecologically unequal exchange theory, focusing on the lead up to and aftermath of the 2015 Paris negotiations. We identify and discuss three areas of tension that have emerged within the G-77 coalition: tensions within the global semi-periphery, tensions between the semi-periphery and periphery, and tensions within the periphery. Together, these tensions challenge the main link of solidarity in the G-77 coalition: the idea that all countries in the global South share a common predicament in the global system, with the North solely to blame. Drawing upon this case, we offer three related insights to develop ecologically unequal exchange theory. First, theory and empirical work must better consider the role of the semi-periphery, and divisions within the semi-periphery, in reproducing ecologically unequal societies. Second, theory should account for how fragmentation between the periphery and semi-periphery may produce distinct challenges for peripheral states to resist governance forms which intensify ecologically unequal exchange. Third, theory should better account for the ways in which ecologically unequal exchange as mobilized as a collective action frame reflects and diverges from the real-world distribution of environmental goods and bads in the world system.